ANALYSIS OF OFFENSIVE AND DEFENSIVE ACTIONS OF YOUNG SOCCER GOALKEEPERS - Santos, João (2021)
Purpose. The study aimed to investigate the defensive and offensive technical tactical actions of elite young football goalkeepers. Methods. The goalkeepers who participated in our study (n = 3; mean age: 16.6 years) had 8 years of experience in the position, were Portuguese, and competed in the Portuguese National Championship U-17. Thirty championship games were observed. The observational instruments used were constructed and validated for the investigation, and the technicaltactical actions were coded with the Lince® software. The data were processed through a descriptive analysis, by using the Microsoft Excel® computer program. Results. Defensive actions with most occurrences were goal defence (25.33 ± 8.14), deviation to punch (13.67 ± 12.5), with 2 hands (45.66 ± 21.38), and in zone 1 (50.33 ± 34.81). Offensive actions started more frequently with delayed pass (38.33 ± 28.01), for zone 1 (28.7 ± 20.60). The goalkeepers executed goal kick most frequently (17.33 ± 14.29), followed by short hand replacement (16.67 ± 12.06) and short pass (14.33 ± 10.02). The preferred pass zone was 9 (17.33 ± 10.26), and actions sought to initiate positional attack (86 ± 61.02). Conclusions. In the defensive process, the goalkeepers’ actions are mostly focused on the objective of goal defence; in the offensive process, technical actions with the hands and feet are important in the participation in positional attack construction.